MANUFACTURING FOAMED CONCRETE AS AN ALTERNATIVE MATERIAL TO REPLACE EMAS (ENGINEERED MATERIALS ARRESTING SYSTEM) - Made Sukrawa; Ida Bagus Rai Widiarsa; I Nyoman Sucika (Jurnal Ilmiah Teknik Sipil, 2024)
The Engineered Material Arresting System (EMAS) serves as a solution to overrun aircraft, particularly on runways with Runway End Safety Area (RESA), thereby enhancing aviation safety. This study involves the fabrication and testing of foam concrete using local materials, including cement, fly ash, and foam, both with and without the addition of fibers. The targetdensity is set at 600 kg/m³. Materials utilized include Gresik PCC cement, Paiton fly ash, AKS brand foaming agent for foam production, and polypropylene fibers (Fosroc PPF M12). The research methodology encompasses literature of review and experimentation. The mix composition for one cubic meter of concrete comprises 300 kg cement, 111 kg fly ash, 135 liters water, and 720 liters foam. In the case of foam concrete with fibers, 2 kg of polypropylene fibers are added for 1 m3 of mix. Test specimens consist of 35 cylindrical specimens measuring 150 mm x 300 mm and 10 plates measuring 400 mm x 300 mm x 83 mm. The test results indicate a foam concrete density of 560 kg/m³ (for foam concrete with polypropylene fibers), slightly below the target of 600 kg/m³. The average compressive strength of specimens without fibers is 1.08 MPa, with a maximum deformation of 13.00 mm. Meanwhile, for foam concrete with fibers, the average compressive strength is 0.53 MPa, with a maximum deformation of 36.50 mm. The inclusion of fibers in foam concrete leads to lower compressive strength but increased ductility, as evidenced by longer deformation. This characteristic makes the addition of polypropylene fibers more suitable for use in EMAS. Consequently, Paiton fly ash, Gresik Portland cement, and foam (AKS foaming agent) can be effectively employed as local materials in the production of foam concrete for EMAS